Analysis of detection range of FM‐based passive radar. Issue 2 (1st February 2014) - Malanowski, Mateusz; Kulpa, Krzysztof; Kulpa, Janusz; Samczynski, Piotr; Misiurewicz, Jacek
Abstract : This study presents an analysis of the detection range of a passive bistatic radar (PBR) by using FM radio transmitters as the illuminators of opportunity and the analysis of a required analogue‐front‐end dynamic range. Firstly, the theoretical considerations are presented in which the power budget is analysed, by taking into account the specific features of the PBR such as instantaneous reception of the direct illumination signal and weak target echoes and direct path interference removal. In the second part of this study, measurements performed by using an FM‐based PBR demonstrator PaRaDe (passive radar demonstrator) are presented. The PaRaDe is a deployable system operating in real time, developed at the Warsaw University of Technology, Poland. The measurements include a scan of a typical spectrum in the range of 88–108 MHz, and the analysis of the long range detection of the air targets.